Innovation in Indonesian Language Learning in Elementary School - Satriana, Satriana; Rahma Ashari Hamzah; Siti Syahraeni (Yayasan Insan Mulia Bima, 2025)
To improve the quality of learning that is more participatory, integrated, and relevant, teachers must act quickly to implement learning innovations. The implementation of digital learning still faces challenges, such as limited internet access, teacher readiness, and the need to adjust content to the curriculum and student characteristics. The purpose of this study is to trigger a comprehensive discussion on how to use technology in teaching Indonesian, modify teaching strategies to accommodate different student learning preferences, and build a fun and satisfying learning environment. The data collection technique for this study uses library research. Research is carried out systematically to collect, process, and conclude data using certain methods/techniques to find answers to the problems faced in the study. Researchers need data from various literature sources in the form of books, previous research journals as sources of research data in order to obtain a theoretical basis for the problems to be studied. This study shows that students can get a more interesting, fun, and in-depth learning experience when interactive learning materials such as digital comics are used together with augmented reality (AR) and virtual reality (VR) technology. Because the content looks more real and dynamic, students are more enthusiastic about following the learning process, which ultimately leads to greater motivation and deeper understanding of concepts. In addition, this method has been proven to reduce student boredom and increase active participation in the learning process.